Economic returns to schooling in a less developed country: evidence for Indonesia - Purnastuti, Losina; Miller, Paul; Salim, Ruhul (Department of Economics and Food Sciences, University of Perugia, Italy, 2011)
The purpose of this study is to provide an update of the empirical evidence on the private return to schooling in Indonesia using sample data from Indonesian Family Life Survey 4 (IFLS 4). The augmented Mincerian model is utilised to quantify the private return to schooling. The main result obtained indicates that the return to schooling in Indonesia is relatively low compare to other Asian and Less Developed Countries. It is also found that return to schooling for females are significantly different from those of males.